Application of Nanoparticles on Diagnosis and Therapy in Gliomas. (17th April 2013) - Hernández-Pedro, Norma Y.; Rangel-López, Edgar; Magaña-Maldonado, Roxana; de la Cruz, Verónica Pérez; Santamaría del Angel, Abel; Pineda, Benjamín; Sotelo, Julio
Abstract : Glioblastoma multiforme (GBM) is one of the most deadly diseases that affect humans, and it is characterized by high resistance to chemotherapy and radiotherapy. Its median survival is only fourteen months, and this dramatic prognosis has stilled without changes during the last two decades; consequently GBM remains as an unsolved clinical problem. Therefore, alternative diagnostic and therapeutic approaches are needed for gliomas. Nanoparticles represent an innovative tool in research and therapies in GBM due to their capacity of self-assembly, small size, increased stability, biocompatibility, tumor-specific targeting using antibodies or ligands, encapsulation and delivery of antineoplastic drugs, and increasing the contact surface between cells and nanomaterials. The active targeting of nanoparticles through conjugation with cell surface markers could enhance the efficacy of nanoparticles for delivering several agents into the tumoral area while significantly reducing toxicity in living systems. Nanoparticles can exploit some biological pathways to achieve specific delivery to cellular and intracellular targets, including transport across the blood-brain barrier, which many anticancer drugs cannot bypass. This review addresses the advancements of nanoparticles in drug delivery, imaging, diagnosis, and therapy in gliomas. The mechanisms of action, potential effects, and therapeutic results of these systems and their future applications in GBM are discussed.